Cryotherapy for low risk prostate cancer, oncological and functional medium term outcomes: A three center prospective study - ŞENER, TARIK EMRE (PAGEPRESS PUBL, 2017)
Objectives: Analyze the oncologic and functional outcomes in patients affected by low risk prostate cancer underwent prostate cryotherapy. Materiasl and methods: It's a prospective tricentric study of 434 patients treated with prostate cryoablation for low risk prostate cancer. By low risk we refer to the D'Amico's risk classification. Two cycles of freezing/thawing are run for each patient following the technique described by Onik. Results: For the 434 patients, the median age was 66 years with a standard deviation of +/- 6.68, the average PSA was 6.17 ng/d/L, the median 5.55 with a standard deviation of +/- 2.13, the mean prostate volume was 35.59 cc, the median 34.00 cc, with a standard deviation of +/- 7.89. Biochemical failure occurred in 67 patients (15.4%). Pre-operative erectile function in men was distributed as follows: severe in 95 patients (19.2%), moderate in 95 (19.2%), medium-moderate in 180 (36.4%), mild in 92 (18.6%), with no dysfunction in 32 (6.5%) patients. Post-operative erectile function, measured 1 month after cryotherapy, was distributed as follows: severe in 321 (65%) patients, moderate in 69 (14%), medium-moderate in 79 (16%), mild in 23 (4.7%), and no dysfunction in only 2 patients (0.4%). Post-operative erectile function after 3 months was distributed as follows: severe in 233 (47.2%) patients, moderate in 66 (13.4%), medium-moderate in 122 (24.7%), mild in 65 (13.2%), and no dysfunction in 8 patients (1.6%). Urinary incontinence was present in 21 patients (4.8%) after 3 months while it dropped to 13 patients (2.9%) after 6 months. Conclusions: Cryotherapy in the treatment of prostate cancer remains a viable alternative. The availability of new cry-oprobes and the use of new diagnostic means such as fusion magnetic resonance will make this more precise and more effective method.
Keywords: Prostate cryotherapy; Minimally invasive treatment; Focal therapy; Low risk prostate cancer; ACTIVE SURVEILLANCE; RADICAL PROSTATECTOMY; RADIATION-THERAPY; CRYOSURGERY; SURVIVAL; TRIAL; MEN